SYMBOLISM AND SOCIAL CLASS CONFLICT IN ”THE PLATFORM” : A QUALITATIVE CONTENT ANALYSIS - Fitria, Ajeng Noor; Probowati, Yeni; Kuswahono, Deny (TELL - US JOURNAL, 2024)
This study provides a comprehensive analysis of the film "The Platform" through the lens of Marxist critique, focusing on its portrayal of social classes and the impact of the capitalist system on social relations. Using a qualitative content analysis approach, the study examines the film's symbolic elements, metaphorical significance, and key dialogues and interactions. The findings reveal how the vertical prison structure symbolizes social hierarchy, with opulent banquets for the upper levels and scraps for the lower levels representing wealth disparity. The random assignment of prisoners each month illustrates the arbitrary nature of social mobility in capitalist societies. Additional symbols, such as Miharu’s search for her child and the act of sending the child back to the top, highlight themes of exploitation and the potential for revolutionary change. The study also explores the metaphorical significance of the vertical prison, critiquing the illusion of meritocracy and the systemic barriers to social advancement. Key dialogues emphasize social tensions, power dynamics, and ethical dilemmas faced by individuals within an exploitative system. This detailed examination extends previous research by providing a nuanced understanding of how "The Platform" critiques capitalist ideologies and highlights systemic social inequalities. The study underscores the film's significance as a critique of capitalist social structures and its potential to inspire discourse on social justice and equity. Future research could explore the film’s impact on audiences and compare it with other dystopian narratives.